Hadith #2878 - Sunan Ibn Majah - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Anas ibn Malik; Muhammad bin Sa'id bin Yazid محمد بن سعيد بن يزيد بن إبراهيم; Shbyb bin Sa'id al-Tmymy شبيب بن سعيد التميمي الحبطي (Sunan Ibn Majah)
“I heard ‘Ubaid bin Fairuz say: ‘I said to Bara’ bin ‘Azib: “Tell us of the sacrificial animals that the Messenger of Allah (ﷺ) disliked or forbade.” He said: “Allah’s Messenger (ﷺ) said like this with his hand. And my hand is shorter than his hand:* ‘There are four that will not be accepted as sacrifices: The one-eyed animal that is obviously blind in one eye; the sick animal that is obviously sick; the lame animal with an obvious limp; and the animal that is so emaciate
Grade:

Hadith #3504 - Sunan Ibn Majah - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Anas ibn Malik; Muhammad bin Sa'id bin Yazid محمد بن سعيد بن يزيد بن إبراهيم; Shbyb bin Sa'id al-Tmymy شبيب بن سعيد التميمي الحبطي (Sunan Ibn Majah)
“A house burned down in Al-Madinah, with its occupants inside. The Prophet(ﷺ) was told of what had happened, and he said: ‘This fire is an enemy to you. When you go to sleep, extinguish it.'”
Grade: